Development of Belawan's "Marsihaholongan" Batak Toba Dance / Script in the Context of a Plural Community in North Sumatra - Tampubolon, Flansius; Pollatu, Maurits Junard (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
North Sumatra is one of the provinces in Indonesia which is quite rich in culture including dance. Dance studio is one part of cultural elements that have educational value in the form of function and role in the midst of plural society. Some people of North Sumatra compile and manage dance studios to preserve traditional arts. One of the existing dance studios is the Toba Batak Dance / Aksara "Marsihaholongan". This dance studio is one of the studios in the Bagan Deli area, Belawan. This dance studio began to be made in 2008 with the aim of a place or facility used by the community or a group of people to conduct training activities, namely activities that focus more on the dance field, both traditional and modern dance. This dance studio was created also as a vehicle for the application of harmony among religious believers, not only based on the field of art, but also based on improving culture in plural societies.